Fire! fire! - Gibbons, Gail. ([New York] : Scholastic, 1992)
A step-by-step description of what happens to mail from the time it is deposited in the mailbox to its arrival at its destination. Also includes brief historical facts about mail service in the United States.
Fire! Fire! is an informational text about fire safety and the role of firefighters. Illustrations are clear and informative and the book contains a list of fire fighting equipment, (3z(Bways to prevent a fire,(3y (Band (3z(Bwhat to do if there is a fire.(3y (BI found this book to be mildly engaging, but believe that it targets a very specific audience (ages 5-9) that would find it exciting.s
Keywords: Postal service -- United States -- Juvenile literature